2022
DOI: 10.1021/acs.nanolett.2c03715
|View full text |Cite
|
Sign up to set email alerts
|

Formation of In-Plane Semiconductor–Metal Contacts in 2D Platinum Telluride by Converting PtTe2 to Pt2Te2

Abstract: Monolayer PtTe2 is a narrow gap semiconductor while Pt2Te2 is a metal. Here we show that the former can be transformed into the latter by reaction with vapor-deposited Pt atoms. The transformation occurs by nucleating the Pt2Te2 phase within PtTe2 islands, so that a metal–semiconductor junction is formed. A flat band structure is found with the Fermi level of the metal aligning with that of the intrinsically p-doped PtTe2. This is achieved by an interface dipole that accommodates the ∼0.2 eV shift in the work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…52 This direction of the E built-in and the band alignments of the two configurations support them to work as a Z-scheme rather than type-II photocatalytic performance. Additionally, the present band alignments and direction of the built-in electric field are similar to those of the p−n heterojunctions containing PtTe 2 or Sb 2 S 3 , 20,24,53 implying that a weak p−n heterojunction may also occur in the present heterostructure. As shown in Figure 3, the E built-in accelerates the recombination of the photogenerated hole at the VBM of the PtTe 2 monolayer and the electron at the CBM of the Sb 2 S 3 monolayer.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…52 This direction of the E built-in and the band alignments of the two configurations support them to work as a Z-scheme rather than type-II photocatalytic performance. Additionally, the present band alignments and direction of the built-in electric field are similar to those of the p−n heterojunctions containing PtTe 2 or Sb 2 S 3 , 20,24,53 implying that a weak p−n heterojunction may also occur in the present heterostructure. As shown in Figure 3, the E built-in accelerates the recombination of the photogenerated hole at the VBM of the PtTe 2 monolayer and the electron at the CBM of the Sb 2 S 3 monolayer.…”
Section: Resultssupporting
confidence: 63%
“…The nanoscale vdW heterostructures with different 2D ultrathin functional nanosheets can often achieve satisfactory photocatalytic performance with a direct Z-scheme if a suitable band alignment is constructed. , Here, we demonstrate that the PtTe 2 /Sb 2 S 3 nanoscale heterostructure can also achieve high η STH ′ with the direct Z-scheme. The PtTe 2 monolayer as a member of the TMD family has been prepared in the experiment and is similar to the synthesized PtTe 2 /Pt 2 Te 2 nanoscale heterostructures . Recently, the potential use of the PtTe 2 monolayer in a variety of different applications, such as electrocatalysis, ultrafast photonics, and terahertz photodetection, has been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…PtTe 2 and PtSe 2 are grown in dedicated tellurium and selenium growth chambers by co-deposition of Pt and chalcogens. First a PtTe 2 multilayer film is grown at 300 °C substrate temperature on a freshly cleaved and vacuum-annealed HOPG substrate. , Subsequently, a monolayer of PtSe 2 is grown on top of the PtTe 2 at a growth temperature of 300 °C. For both compounds, Pt was evaporated in an e-beam evaporator from a 2 mm solid Pt rod.…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional (2D) transition metal dichalcogenides (TMDs) semiconductors have presented great potential as the channel materials for field effect transistors (FETs) due to their high carrier mobility and large on/off ratio. TMDs-based FETs have been widely investigated and have demonstrated that they are advantageous over the other nanomaterial-based FETs, which are attributed to the dangling-bond-free surface and the moderate band gaps of TMDs. However, the contact between metal electrodes and TMDs is inevitable. The Schottky barrier is commonly formed at the contact interface, which will impede the charge injection efficiency. Thus, reducing the Schottky barrier height (SBH) is desirable for designing the high-performance electrical devices.…”
Section: Introductionmentioning
confidence: 99%